Design and Experimental Validation of qPCR Primer for Drought-Responsive CaHsfA2 Gene in Capsicum annuum for Sustainable Crop Production - Suwirmen; Zozy Aneloi Noli; Anthonie Agustien; Djong Hon Tjong; Amanda Nurhafitri (Postgraduate, University of Mataram, 2026)
Drought stress severely reduces plant productivity by disrupting photosynthesis and cellular homeostasis. Plants respond through regulatory networks involving stress-responsive genes, including heat shock proteins (HSPs), regulated by heat shock transcription factors (HSFs). Among these, HsfA2 plays an important role in abiotic stress tolerance, including drought. Although CaHsfA2 expression has been reported in Capsicum annuum, validated primers for quantitative PCR (qPCR) analysis remain limited. This study aimed to design and validate specific primers for CaHsfA2 expression analysis. Primer candidates were designed from sequence NM_001324561.1 using Primer-BLAST and evaluated based on length, GC content, melting temperature (Tm), and self-complementarity. Total RNA was extracted from chili roots subjected to drought stress (50% field capacity) and nanopriming with Padina minor, followed by cDNA synthesis, gradient PCR and agarose gel electrophoresis.. Secondary structures were analyzed using OligoAnalyzer. Of ten primer pairs, four met the criteria, and primer set 1 (1_CaHsfA2) showed optimal characteristics (%GC 55%, Tm 60°C, product length 190 bp) and minimal secondary structure potential (ΔG > −9 kcal/mol). Gradient PCR (55.3–59.2°C) produced a single band ( 193 bp), consistent with the predicted size (190 bp), with an optimal annealing temperature of 57.3°C, confirming its specificity and suitability for qPCR-based gene expression analysis under drought conditions.